Enter a number in each box so that the expressions are equivalent. (A) 0.8 (2x + x) + 3(7 - 4.1x) = x + 21 (B) 12 1 2 (6x + 22y) = x + y (C) (3x - ) - (6x + 1) = -3x - 2 (D) 112 1 2 x + 27y = (12 1 2 x + 9y)

Respuesta :

fichoh

The questions aren't well formatted ; from the values that are observable,

Answer:

Coefficient of x = -9.9 ;

Coefficient of x = 75

Coefficient of y = 275

Step-by-step explanation:

Given :

0.8 (2x + x) + 3(7 - 4.1x) = __x + 21

0.8(3x) + 21 - 12.3x = __x + 21

2.4x + 21 - 12.3x = __x + 21

-9.9x + 21 = __x + 21

-9.9

12 1/2 (6x + 22y) = x + y

75x + 275y = x + y

Answer:

The answers are:

1.  -9.9x

2.  3x + 11y

3.  1

4.  3

Ver imagen prialsebastian